The involvement of the primo vascular system in local enteritis and its modification by electroacupuncture - Nan, Sha; Wan, Juan; Lei, Qianghui; Wang, Xinya; Ma, Ning; Yin, Ruiling; Zhu, Jiandi; Ding, Mingxing; Ding, Yi (Frontiers in Immunology, 2023)
The primo vascular system (PVS), an intensive network structure, was claimed to be a representative of acupuncture meridian. Here, we explored the role of PVS in local enteritis, and its modification by acupuncture. Chronic cecitis in rabbits was induced by 2,4,6-trinitro-benzene-sulfonic acid (TNBS). PVS on the cecum was visualized with trypan blue staining, and collected with the help of microsurgical forceps under an optical stereomicroscope. The increased primo vessels (PVs) and primo nodes (PNs) of the PVS on the surface of the cecum were induced by the local inflammation, which were positively correlated with the inflammatory cells in the cecal mucosa. Tandem mass tag (TMT) based proteomic analysis revealed that 110 differentiated proteins of PVS existed between TNBS-treated and control rabbits; 65 proteins were upregulated while 45 proteins were downregulated. These proteins were mainly enriched in inflammation- and immunity-related processes such as inflammatory cell proliferation, antigen presentation and cell adhesion in the proliferated PVS (data are available via ProteomeXchange with the identifiers PXD034280). Importantly, TNBS-induced cecitis, and proliferated PVS and inflammation response-related proteins (CD40, CD45, HLA-DRA1, LAMP1, JAGN1 and FGL1) in the PVS were alleviated or reversed by repetitive electroacupuncture (EA) stimulations. These results suggested that proliferated PVS and its active inclusions were related to the inflammatory process, which were modified by EA. Our study provides a new avenue to further explore mechanism by which EA exerts anti-inflammatory effect.